Competition in Healthcare: Good, Bad or Ugly? - Goddard, Maria (Int J Health Policy Manag, 2015)
The role of competition in healthcare is much debated. Despite a wealth of international experience in relation to competition, evidence is mixed and contested and the debate about the potential role for competition is often polarised. This paper considers briefly some of the reasons for this, focusing on what is meant by "competition in healthcare" and why it is more valuable to think about the circumstances in which competition is more and less likely to be a good tool to achieve benefits, rather than whether or not it is "good" or "bad," per se.M